Lactobacillus paracasei HII01, xylooligosaccharide and synbiotics improve tibial microarchitecture in obese-insulin resistant rats - Sathima Eaimworawuthikul (2019)
© 2019 Elsevier Ltd High-fat diet (HFD)-induced obese-insulin resistance negatively affects bone via gut microbiota dysbiosis-triggered systemic inflammation. The biotic treatment can improve metabolic status in HFD-fed rats. However, the microarchitectural analysis by bone histomorphometry of the tibia have not been determined. Forty-eight male Wistar rats were fed with normal diet or HFD for 24 weeks. At week13, rats were received either a vehicle, Lactobacillus paracasei HII01, xylooligosaccharides, or synbiotics. Blood analyses and tibial histomorphometry were performed. We found that L. paracasei HII01, xylooligosaccharides, and synbiotics improved obese-insulin resistance and systemic inflammation in HFD-fed rats. These biotics equally increased bone volume fraction and trabecular thickness, reduced osteoclast surface and active erosion surface, increased the double labeled surface, mineralizing surface, mineral apposition rate and bone formation rate of HFD-fed rats. In conclusion, these biotic therapies exerted an enhancement of bone microarchitecture in HFD-fed rats possibly by mitigating osteoclast-mediated bone resorption and promoting osteoblast-induced bone formation.